Dietary modulation of antimicrobial peptides ( HAMP and LEAP2 ) in Chinook salmon ( O ncorhynchus tshawytscha ) fed a phytobiotic functional diet: Integrated genomic characterisation and tissue‐specific expression - Roberta Marcoli; Jane E. Symonds; Seumas P. Walker; Cesar Lopez; Mark A. Preece; Christopher Battershill; Steve Bird (Journal of Fish Biology, 2026)
Antimicrobial peptides (AMPs) are key components of the innate immune system in fish, providing rapid protection against microbial pathogens. Among these, the liver‐expressed antimicrobial peptides (LEAPs), comprising LEAP‐1 (hepcidin; HAMP) and LEAP‐2, play central roles in host defence and iron regulation. In this study, we present an integrated characterisation of the genomic organisation, tissue expression and dietary responsiveness of HAMP and LEAP2 paralogues in Chinook salmon ( Oncorhynchus tshawytscha ), and assess their modulation by a phytobiotic functional feed under commercial farming conditions. Genome mining identified three functional HAMP and three LEAP2 paralogues in Chinook salmon, all retaining conserved features typical of their respective peptide families and arising from salmonid‐specific genome duplication events. Constitutive expression analysis revealed liver‐dominant expression of HAMP, whereas LEAP2 paralogues exhibited distinct tissue‐specific profiles, with LEAP2.1 and LEAP2.2 expressed predominantly in the liver and skin, and LEAP2.3 largely restricted to gills and skin. A six‐month feeding trial using a functional diet supplemented with the phytobiotic NatControl™ resulted in marked tissue‐ and paralogue‐specific upregulation of AMP gene expression. HAMP expression was upregulated across multiple immune‐relevant tissues, including head kidney, skin, spleen, liver and gills. LEAP2 paralogues also showed clear dietary responsiveness, with LEAP2.1 and LEAP2.2 upregulated in the liver and kidney, and LEAP2.3 showing strong upregulation in gills. Despite these molecular responses, no significant differences in growth or survival were observed between diet groups. Together, these findings provide the first integrated characterisation of HAMP and LEAP2 systems in Chinook salmon, demonstrate their sensitivity to dietary immunomodulation and support their use as molecular biomarkers of functional immune priming. The results further indicate that NatControl™ acts as an effective immunostimulant, enhancing innate immune readiness without compromising growth performance under non‐challenging conditions.

Recovery of ecosystem carbon pools 35 years after whole-tree and stem-only clearcutting a red spruce – balsam fir forest in north-central Maine, USA - Inge Stupak; Bruna Barusco; Russell D. Briggs; Ivan J. Fernandez; Shawn Fraver; Agnė Grigaitė; Christopher Preece; Brian E. Roth; C. Tattersall Smith (Forest Ecology and Management, 2025)

A versatile transgenic allele for mouse overexpression studies - Hamid Dolatshad; Daniel Biggs; Rebeca Diaz; Nicole Hortin; Christopher Preece; Benjamin Davies (Mammalian Genome, 2015)